Mobile Modular Hydrogen Power Generation a Zero Carbon Energy System - Abbott, Marc (International Journal of Global Sustainability, 2023)
The transition to a zero-carbon energy system is inevitable if society is to negate CO2 emissions associated causes of Climate Change and replace the usage of our finite hydrocarbon resources. The transition to a zero-carbon energy system will take decades to not only replicate the scale and efficiency of our existing energy system but to also develop the technologies needed that on a like for like basis will provide society with at least comparing with today a zero-carbon energy system that is efficient and cost effective. This short communication puts forward a potential solution that is efficient, cost effective and most importantly zero-carbon emissions. The intent is to give an overview of the technologies that can achieve this with their respective current technical readiness and timeline to full scale public deployment.